Recombinant proteins as promising antigens applied to the immunodiagnosis of Chagas disease: a scoping review - Resende, Carlos Ananias Aparecido; Ribeiro, Anna Júlia; Gandra, Isadora Braga; Silva, Kamila Alves; Lopes, Lucas da Silva; Barcelos, Isabelle Caroline dos Santos; Couto, Carolina Alves Petit; de Faria, Mariana Teixeira; Pereira, Sabrina Paula; Xavier, Sandra Rodrigues; Machado, Juliana Martins; da Paz, Mariana Campos; et al. (Frontiers in Microbiology, 2024)
Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is an important public health problem, occurring mainly in Latin America. The disease has a major social and economical effect, negatively impacting the life of the infected individuals, and bringing great costs to public health. An early and accurate diagnosis is essential for administration of early treatment. In addition, prognostic tests may aid disease management, decreasing hospitalization costs. However, the serological diagnostic scenario for CD still faces several challenges, making the development of new diagnostic kits a pressing matter. Facing this scenario, several researchers have expanded efforts in developing and testing new antigens, such as recombinant proteins and recombinant multiepitope proteins, with promising results. These recombinant antigens offer several advantages, such as improved sensitivity and specificity, in addition to facilitated scaling. Also, it has been possible to observe a rising number of studies using ELISA and point-of-care platforms, employing these antigens in the past few years. Among them, recombinant proteins were the most applied antigens, demonstrating great capacity to Excluído: promise 42 Excluído: .